SUPPORTING STAGED INTIMACY a practical guide for theatre creatives, managers, and crew. - Black, Alexis; Newhauser, Tina M. ([S.l.] : FOCAL, 2022)
Supporting Staged Intimacy: A Practical Guide for Theatre Creatives, Managers, and Crew examines the relationship between staged intimacy, intimacy direction, and those supporting the process during pre-production, rehearsal, and performance. First, this book addresses challenges and trends in staging intimacy, helping backstage and offstage theatre artists recognize the problematic approaches and culture that led to the emerging field of intimacy direction. This text will then provide tools and recommended practices for supporting the creation and maintaining of staged intimacy, enabling team members to enact contemporary protocols concerning advocacy and agency. Finally, this book will educate and empower readers with the necessary skills to prompt change; by providing modern techniques, essential workplace protocols, and achievable action items, this book will transform the way theatre designers, managers, crew, and other creative team members engage with theatrical consent. Supporting Staged Intimacy is written for every pre-professional and professional artist working behind the scenes who wish to better support consensual workplaces, physically intimate stories, and the individuals telling those stories.
Keywords: Intimacy (Psychology) in the theater; Theater -- Psychological aspects; PERFORMING ARTS / Theater / Direction & Production; PERFORMING ARTS / Theater / Stagecraft